If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(2 + -1x) + x(x + 1) = 5 (2 * 3x + -1x * 3x) + x(x + 1) = 5 (6x + -3x2) + x(x + 1) = 5 Reorder the terms: 6x + -3x2 + x(1 + x) = 5 6x + -3x2 + (1 * x + x * x) = 5 6x + -3x2 + (1x + x2) = 5 Reorder the terms: 6x + 1x + -3x2 + x2 = 5 Combine like terms: 6x + 1x = 7x 7x + -3x2 + x2 = 5 Combine like terms: -3x2 + x2 = -2x2 7x + -2x2 = 5 Solving 7x + -2x2 = 5 Solving for variable 'x'. Reorder the terms: -5 + 7x + -2x2 = 5 + -5 Combine like terms: 5 + -5 = 0 -5 + 7x + -2x2 = 0 Factor a trinomial. (-5 + 2x)(1 + -1x) = 0Subproblem 1
Set the factor '(-5 + 2x)' equal to zero and attempt to solve: Simplifying -5 + 2x = 0 Solving -5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 0 + 5 2x = 0 + 5 Combine like terms: 0 + 5 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {2.5, 1}
| 5x+2+4x-8+2x-12=180 | | 64t^3=9t | | 0.09x+0.02(x+3)=1.27 | | 4x+0+x+12=x+12 | | Y=4x^2+4x-420 | | 6-(2+3a)+4a=-3(a-2)-4 | | z^2=25 | | 2(x-11)=-10 | | x+19+2x+2+8x-19=180 | | 3k-1+2=10 | | 165-7x=20x+18 | | 5x+3-2x=-12 | | -8+7p=6 | | 3x+71+5x+37=180 | | 11-9x=155-37x | | 25=7-2z | | 5x^2-19+24=0 | | 5y-11=38 | | 10x-16+4x+1+x+0=180 | | 5y-11=-38 | | x+54+x+23=180 | | 4+4n=28 | | 3x+8+x-1+6x-17=180 | | 2x+5+-3x-3=9 | | 12000=5000 | | 54/3=x | | 16=-9u-6+7u | | 73-4x=41x+23 | | 4(n+(n+4))=3(n+2)+5 | | 2x-3+5x-1+8x+19=180 | | 15.55=4.95 | | x=3+0,5x |